METHYL PARATHION IMPACT ON THE ESTERASES OF A FRESHWATER TELEOST TILAPIA MOSSAMBICA (PETERS) - Rao, K Siva Prasada; Rao, K R S Sambasiva; Prasad, K Sathya; Rao, K V Ramana (Indian Journal of Fisheries, 2011)
Acetylcholinesterase activity decreased in muscle, gill, liver and brain tissues of T. mossambica with a corresponding increase in acetylcholine content following methyl parathion exposure, suggesting a disruption in the nerve impulse conduction. The electrophoretic study of esterases in the various tissues of Tilapia mossambica suggests that there are about six anodally migrating bands and there is an inhibition of esterase bands in muscle, gill, liver and brain tissues during subacute methyl parathion impact and it is found to be tissue specific